PENGARUH MOTIVASI KERJA KARYAWAN TERHADAP KINERJA PEGAWAI PADA PT NIPPON INDOSARI CORPINDO, TBK - Rizqi Yosia Siringo Ringo; Puji Isyanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The study took place at PT Nippon Indosari Corpindo and explores the intricate connection between employee motivation and productivity, focusing particularly on variables like rewards, incentives, and job roles that influence their performance. Based on a review of existing literature, the research indicates that motivation plays a crucial role in enhancing employee productivity. Additionally, this article examines the impact of leadership style and work discipline on employee performance. Findings from the study indicate that motivated employees generally exhibit increased productivity. Factors contributing to motivation encompass economic considerations, work ethics, personal backgrounds, and individual traits. This suggests that to boost productivity, companies should cultivate a work environment that encourages employee happiness and contentment, and provides effective motivation, which includes adequate financial incentives. This article proposes that prioritizing motivation can serve as an effective approach for companies aiming to enhance overall employee performance. The author offers valuable perspectives for organizations seeking to improve efficiency and effectiveness by adopting sustainable motivation strategies that prioritize employee well-being.